2002
DOI: 10.2174/1386207023330192
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Affinity Chromatography for the Screening of Mixtures

Abstract: A protein stationary phase for frontal affinity chromatography was prepared, containing biotinylated beta-galactosidase immobilized to controlled pore glass beads via covalently bonded streptavidin. Single microaffinity columns of approximately 30 pmol of active beta-galactosidase were prepared from this material and characterized with a known ligand by frontal analysis. These columns were used to measure the specific interactions between the bound beta-galactosidase and a library of modified beta-galactopyran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…FAC assays require that the buffer conditions for maximum activity and minimum interference with the desorption/ionization process at the ESI interface be optimized. Recently, a FAC/MS study of a library of 356 compounds targeted to ␤-galactosidase revealed 34 substances with dissociation constant values lower than 10 µM (14). However, not all of the tested compounds could be detected by ESI-MS; therefore, other ionization modes such as atmospheric pressure chemical ionization or MALDI may be needed to complement future assays.…”
Section: Other Methodsmentioning
confidence: 99%
“…FAC assays require that the buffer conditions for maximum activity and minimum interference with the desorption/ionization process at the ESI interface be optimized. Recently, a FAC/MS study of a library of 356 compounds targeted to ␤-galactosidase revealed 34 substances with dissociation constant values lower than 10 µM (14). However, not all of the tested compounds could be detected by ESI-MS; therefore, other ionization modes such as atmospheric pressure chemical ionization or MALDI may be needed to complement future assays.…”
Section: Other Methodsmentioning
confidence: 99%
“…The concentration of the weaker ligand increases transiently above its infusion level; this is caused by the action of the slower-eluting stronger ligand. When the stronger ligand enters a region through which the weaker ligand has passed, it re-establishes the local equilibrium and displaces the weaker ligand (14,15). This wave, or roll-up, is a unique and useful feature that can be used to extract information from very complex mixtures.…”
Section: Data Collection and Treatmentmentioning
confidence: 99%
“…FAC/MS is ideally suited for this purpose and can be applied to pooled combinatorial libraries or even natural product extracts. In a model system designed for a library with a high "hit rate", we screened a 356-member library of modified ␤-galactopyranosides with a FAC column containing immobilized ␤-galactosidase enzyme (15). Mixtures of 24 -40 compounds were infused, and the effluent was detected by online MS.…”
Section: Discovering Molecular Interactionsmentioning
confidence: 99%
“…FAC-MS can also be used in a more rigorous mode for determining equilibrium binding constants, K d , of individual compounds. 8 The principles of the FAC-MS screening technique have been described elsewhere [5][6][7][8][9] but will be briefly summarized. It is based on the continuous infusion of small molecules over a protein target immobilized onto a solid support column followed by MS detection.…”
Section: Introductionmentioning
confidence: 99%